The Role of Islamic Pedagogy in Shaping Contemporary Educational Thought: An In-Depth Analysis of Islamic Thought in Modern Education Systems - Mukhlis Mukhlis; Muhammad Eissawy Abu El Yazid; Ahmad Faizal Syahrul Azmi Azmi; Ahmad Fauzan Akbar; Ahmad Nabriz (Ar-rayyan: Journal Of Islamic Education, 2025)
This study explores the role of Islamic pedagogy in shaping contemporary educational thought, particularly within modern education systems that increasingly demand holistic, ethical, and transformative learning frameworks. The research aims to identify the core pedagogical principles rooted in Islamic intellectual tradition and examine their relevance to modern educational discourses. Using a library research method, the study analyzes classical and contemporary texts, educational theories, and scholarly interpretations related to Islamic pedagogy. The findings reveal that Islamic pedagogy offers rich contributions to contemporary education, especially in areas of character formation, integrative knowledge, learner-centered approaches, and ethical reasoning. Furthermore, the study highlights the alignment between Islamic pedagogical concepts and modern educational reforms that emphasize moral education, critical thinking, and humanization. Overall, the research concludes that Islamic pedagogy holds significant potential for enriching global educational thought when articulated through contemporary academic dialogue